The Principal’s Leadership Strategy in Improving the Quality of Teachers’ Performance - Hartati, Siti; Ahmad, Syarwani; Suherman, Suherman (Journal of Social Work and Science Education, 2025)
This study aims to investigate the leadership strategies employed by the principal to enhance teacher performance at MAN 1 Banyuasin and to analyze the obstacles encountered, along with the solutions implemented to address them. The research utilized a qualitative descriptive-analytical approach. Data were gathered through in-depth interviews, direct observation, and documentary analysis involving the principal, teachers, and relevant administrative staff. The findings reveal that the principal’s strategies for improving teacher performance included enforcing discipline, providing motivation, exemplifying leadership qualities, and conducting instructional supervision. However, several significant obstacles were identified: teacher absenteeism and tardiness, lack of intrinsic motivation, inadequate response to leadership modeling, infrequent supervision (only once a year), insufficient infrastructure, and ineffective supervisory support. To address these challenges, the principal implemented measures such as strengthening disciplinary protocols, integrating motivational approaches into human resource development, increasing supervisory frequency to quarterly cycles, and coordinating with stakeholders to improve learning infrastructure. This study offers a contextual and grounded perspective on educational leadership within an Indonesian madrasah setting, highlighting the complex interplay between leadership strategies and practical constraints. It emphasizes the adaptive and problem-solving role of principals in resource-limited environments. The research provides an actionable framework for school leaders to enhance teacher performance by combining disciplinary measures with motivational support, increasing supervisory regularity, and fostering collaboration with government and community bodies to address infrastructural gaps. It underscores the importance of persistent and multifaceted leadership approaches. This study contributes to the field of educational leadership by illustrating how effective leadership strategies can be tailored to overcome specific contextual challenges. It offers valuable insights for policymakers, school administrators, and teacher development programs aiming to improve educational outcomes in similar settings.